Strategic Youth Management: Returning the Youth to Church in Australia - Awuku-Gyampoh, Ransford Kwabena; Sarpong-Akoto, Justina (Advances in Social Sciences Research Journal, 2021)
In a brief review of scholarship, this paper presents the general assessment of Church decline among the Youth in Australia. Journals, books, magazines, and websites information were the resources employed in the analyses. It was discovered that the spiritual and personal growth, discipleship role, and mission life/work determine the young adult’s understanding of the church and environment. Lack of interest, busy life schedule, political issues, and people-pleasing were found to have triggered why the young ones have declined in their church attendance. The review recommended that effective youth ministry is possible if there is a specific and time slot for busy life schedule people; pastors adopt strategic ministry to the youth and focus on enhancing the youth’s philosophical thoughts. The findings would help appropriate youth ministry in the contemporary context. Future researchers may consider the explanatory or exploratory mixed-methods design.